The INF treaty and the new hypersonic revolution - Herrera, M. (Spanish Institute of Strategic Studies, 2019)
Since the beginning of the 21st century, there has been a tendency to abandon arms control agreements. Therefore, the withdrawal´s announcement by the U.S. and Russia from the INF (Intermediate-Range Nuclear Forces) treaty is simply an evidence of the consolidation of this trend. The withdrawal of both powers from the treaty is also an evidence that the non-proliferation regime, and in particular the arms control regime, is gradually crumbling. The possibility of technological advances used to gain an advantage over adversaries and the lack of resolution of discrepancies between nuclear powers encourages the development of new weapons, strategic revisions, and the abandonment of arms controls. This article seeks to analyse three issues: First, to explain the reasons why both the U.S. and Russia have decided to abandon the INF treaty. Second, to explain the implications of such an exit for international security in terms of the development of hypersonic weaponry by Russia, China and the U.S. And thirdly, to analyse where Europe stands, what its new security risks are from now on and what decisions should be taken to tackle them.